2022
DOI: 10.3390/app122412746
|View full text |Cite
|
Sign up to set email alerts
|

Application of Digital Twin in Handling and Transportation of Hazardous Chemicals

Abstract: In China, the Ministry of Transport stressed the need to “Strengthen the application of active safety technology”. The transportation of hazardous chemicals represented by LNG, LPG, and liquefied hydrocarbons is the weak link in traffic safety. The aim of this study is to apply digital twin (hereinafter referred to as DT) technology to the whole process of handling (including loading and unloading) and transportation of hazardous chemicals to help improve the anti-risk ability of road networks at all levels. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The second problem is the need for more aggregation of the whole industrial chain and the whole scene of disaster sources. Li et al [84] aimed to apply DT technology to the entire process of handling and transportation of hazardous chemicals to help improve the anti-risk ability of road networks at all levels. Khan et al [85] indicated that a focused and comprehensive solution is needed, encompassing all aspects, including the early detection, prevention, recovery and management of disaster scenarios to minimize losses.…”
Section: Intelligent Technologies For Disaster Managementmentioning
confidence: 99%
“…The second problem is the need for more aggregation of the whole industrial chain and the whole scene of disaster sources. Li et al [84] aimed to apply DT technology to the entire process of handling and transportation of hazardous chemicals to help improve the anti-risk ability of road networks at all levels. Khan et al [85] indicated that a focused and comprehensive solution is needed, encompassing all aspects, including the early detection, prevention, recovery and management of disaster scenarios to minimize losses.…”
Section: Intelligent Technologies For Disaster Managementmentioning
confidence: 99%